Effect of Alkaline Protease on the Antigenic Nature of Wiseana Nuclear Polyhedrosis Virus Polyhedron Protein - Crawford, A. M. (1977)
Polyhedron protein from Wiseana spp. nuclear polyhedrosis virus was found to be degraded by an alkali protease when polyhedra are dissolved in alkali. The protease activity did not occur at high pH (0.1 M NaOH) and was inactivated by heating polyhedra to 70°C for 3 h. The products from the protease degradation of Wiseana spp. nuclear polyhedrosis virus polyhedron protein retain the antigenicity of undegraded polyhedron protein as measured by the direct solid-phase radioimmunoassay and immunoadsorption. Degradation products below 27,000 daltons could not be detected by the sandwich radioimmunoassay, indicating that they are probably monovalent.